Electromagnetic shielding material capable of realizing intelligent temperature control and preparation method thereof
By combining the Ag/LSW base layer with the VO2/PCM layer composite material, the performance degradation of electromagnetic shielding materials in the prior art under high temperature environment is solved, effective shielding of electromagnetic waves and autonomous thermal management are achieved, and the service life of the equipment is extended.
Patent Information
- Application Number
- CN202411897270.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The prior art is difficult to effectively apply electromagnetic shielding materials in the aerospace, military and medical fields, and the heat generated by these materials when absorbing or losing electromagnetic wave energy is difficult to effectively manage, resulting in reduced equipment performance and shortened service life.
The Ag/LSW base layer and VO2/PCM layer composite material are used. The Ag/LSW base layer is obtained by composite of Ag and modified leather waste through a binder, and has a three-dimensional porous structure; VO2 and phase change energy storage material are fixed by phase change energy storage material to form VO2/PCM composite material and are composited onto the surface of the Ag/LSW base layer.
It realizes effective shielding and autonomous thermal management of electromagnetic waves, and can achieve intelligent temperature control in electromagnetic wave scenarios, extend the service life of the equipment and improve performance.
Smart Images

Figure CN119677085A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of multifunctional composite materials, and relates to an electromagnetic shielding material capable of realizing intelligent temperature control and a preparation method thereof. Background Art
[0002] With the rapid development of electronics and the Internet of Things, a large number of large electronic devices have been built in the environment. The electromagnetic waves generated by the equipment can easily interfere with and damage the normal operation of other electronic devices. Low-resistance metal conductors are widely used as electromagnetic shielding materials through reflection and refraction. However, their high density, easy corrosion and difficult processing characteristics limit their development and application in the aerospace, military and medical fields.
[0003] People have been committed to developing new lightweight shielding devices. The heat generated by a large amount of electromagnetic waves when they are absorbed or lost is difficult to remove. Excessive operating temperature will reduce the performance and service life of electronic equipment, so effective heat dissipation is essential to maintain daily operation. However, simple thermal management materials cannot effectively protect equipment, and there is an increasing need for intelligent electromagnetic shielding materials that can adjust temperature autonomously.
[0004] Natural leather is a natural material composed of collagen fiber bundles. It has great economic value because of its wide source and excellent performance. However, a large amount of leather solid waste will appear in the process of leather manufacturing. Traditional treatment methods such as direct landfill and burning will damage the natural environment. The abundant amino acid residues in leather collagen fibers can act as electric dipoles to generate natural dipole moments. The dipole moments spontaneously align along the direction of the electric field in the electric field. Due to the hindrance of molecular thermal motion, electric dipole relaxation occurs, thereby converting radio wave energy into heat energy through the absorption mechanism. However, the shielding performance of pure leather is not significant enough, and it is necessary to enhance the shielding effect by constructing a conductive layer on the surface. For example, Zeng et al. prepared a new type of foldable solid leather waste (LSW) / polyvinyl alcohol (PVA) / silver (Ag) paper with excellent EMI shielding ability by using a simple chemical plating (ELP) method. They successfully constructed Ag on leather and achieved improved shielding performance (see Zeng, Shulong et al. "From Waste to Wealth: A Lightweight and Flexible Leather Solid Waste / Polyvinyl Alcohol / Silver Paper for Highly Efficient Electromagnetic Interference Shielding." ACS applied materials & interfaces 12.46 (2020): 52038–52049); however, this material cannot have the function of self-intelligent temperature control. Based on this, Shi et al. developed a multifunctional material of solid waste / polyvinyl alcohol multi-source layered composites, further demonstrating the potential of leather collagen fiber microstructure regulation and using 3D porous structures for crude oil adsorption (see Shi, Hao et al. "Multifunctional Silver Decorated Leather Solid Waste / Poly (Vinyl Alcohol) Nanocomposites for Electromagnetic Interference Shielding, Joule Heating and Crude-Oil Cleaning." ACS sustainable chemistry & engineering 10.39 (2022): 13165–13175); however, this material can achieve rapid heating with energy, but it is not smart enough to achieve effective heat management.
[0005] Phase change materials (PCMs) can store and release energy in the form of latent heat while maintaining a constant temperature, and are considered to be the best temperature control materials for thermal protection. By selecting a PCM with a reasonable phase change temperature, the operating temperature of electronic devices can be controlled within a reasonable range. Most of the PCMs composited by microencapsulation and chemical cross-linking methods reported so far have problems such as complex preparation processes and high costs, which seriously limit their large-scale industrialization. In contrast, the use of adsorption technology to assemble PCMs with porous support materials is considered to be a promising method to overcome the above challenges and promote the large-scale preparation of high-performance PCMs. Although simple phase change materials (PCMs) can play a role in storing heat, this is not enough to achieve intelligent temperature control of the material itself. Vanadium dioxide (VO 2 ) is an ideal material for intelligent thermal control systems due to its thermotropic properties. 2 At a critical temperature of about 68°C, VO has a semiconductor-to-metal phase transition, which makes 2 In practical applications, the transition from a transmitted wave to a strongly reflected wave can be used as a "switch" for temperature control. 2 The processing is also very difficult. How to achieve temperature control while also facilitating VO 2 Processing is also a technical problem that needs to be solved.
[0006] In summary, the research and development of new materials that can effectively shield electromagnetic waves and achieve autonomous temperature control is a key technical issue that needs to be urgently solved in this field. Summary of the invention
[0007] The purpose of the present invention is to provide an electromagnetic shielding material that can realize intelligent temperature control in order to solve the above-mentioned problems existing in the prior art, which can not only realize effective shielding of electromagnetic waves, but also has excellent autonomous thermal management performance.
[0008] Another object of the present invention is to provide a method for preparing the electromagnetic shielding material that can achieve intelligent temperature control.
[0009] In order to achieve the above object, the present invention adopts the following technical solutions to achieve it.
[0010] The electromagnetic shielding material capable of realizing intelligent temperature control provided by the present invention comprises an Ag / LSW substrate layer, a phase change energy storage material absorbed into the Ag / LSW substrate layer, and a VO2O3 adsorbed on the surface of the Ag / LSW substrate layer. 2 The Ag / LSW substrate layer is obtained by compounding Ag and leather waste with a binder.
[0011] In the above electromagnetic shielding material, the Ag / LSW base layer presents a three-dimensional porous structure.
[0012] In the Ag / LSW base layer, the leather waste (LSW) is the waste obtained during the commercial chrome tanning process. The leather waste is leather waste powder modified by polydopamine; the dopamine can be replaced by vitamin C or catechol. The leather waste can be replaced by cellulose, palm leather, Lino leather, etc. The mass ratio of Ag to unmodified leather waste (LSW) is 1.8 to 2.0:1. The binder used to bond Ag and leather waste is one of polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), carboxymethyl cellulose (CMC), polyacrylic acid (PAA), etc.
[0013] The phase change energy storage material absorbed in the Ag / LSW substrate layer accounts for at least 20% of the total mass of the Ag / LSW substrate layer and the absorbed phase change energy storage material; in a preferred implementation, the phase change energy storage material absorbed in the Ag / LSW substrate layer accounts for 20% of the total mass of the Ag / LSW substrate layer and the absorbed phase change energy storage material until the phase change energy storage material reaches a saturated state; further, the phase change energy storage material absorbed in the Ag / LSW substrate layer accounts for 20% to 26% of the total mass of the Ag / LSW substrate layer and the absorbed phase change energy storage material. The phase change energy storage material is paraffin, coconut oil or dodecanol, etc.
[0014] The present invention also provides a method for preparing the electromagnetic shielding material capable of realizing intelligent temperature control, which comprises the following steps:
[0015] (1) Preparation of Ag / LSW substrate layer, including the following steps:
[0016] (11) preparing leather waste powder and modifying it by polydopamine to obtain modified leather waste powder;
[0017] (12) preparing solution A: under stirring, adding aqueous ammonia to the silver nitrate solution until the solution becomes transparent to obtain solution A;
[0018] (13) preparing solution B: mixing glucose, tetrahydrate, potassium sodium tartrate, polyethylene glycol and anhydrous ethanol in water to obtain solution B;
[0019] (14) mixing the modified leather waste powder with solution A and solution B, stirring and mixing evenly, and then standing for 6 to 8 hours, and then washing and drying to obtain an Ag / LSW composite material;
[0020] (15) uniformly dispersing the Ag / LSW composite material in water, and then vacuum filtering the obtained dispersion to obtain an Ag / LSW composite film; the Ag / LSW composite film is fixed by a binder to obtain an Ag / LSW substrate layer;
[0021] (2) VO 2 Preparation of PCM composite materials
[0022] VO 2 and phase change energy storage material at a temperature higher than the melting point of the phase change energy storage material to obtain VO 2 / PCM composite materials;
[0023] (3) Ag / LSW substrate and VO 2 The method of preparing electromagnetic shielding materials by composite material of PCM composite material includes the following steps:
[0024] (31) At an ambient temperature higher than the melting point of the phase change energy storage material, the phase change energy storage material is absorbed into the Ag / LSW substrate layer;
[0025] (32) At an ambient temperature higher than the melting point of the phase change energy storage material, the VO obtained in step (2) 2 The / PCM composite material is compounded onto the surface of the Ag / LSW substrate layer and cooled at room temperature to obtain the electromagnetic shielding material.
[0026] The purpose of the above step (1) is to construct an Ag / LSW substrate layer with a three-dimensional porous structure by chemical silver plating. First, a modified leather waste powder is prepared, and then a solution containing Ag is prepared. Then, silver ions are reduced and deposited on the surface of the modified leather waste powder to form a dense silver layer. The formation mechanism is the following redox reaction:
[0027] CH 2 OH(CHOH) 4 CHO+2Ag(NH 3 ) 2 OH→CH 2 OH(CHOH) 4 COONH 4 +2Ag+3NH 3 +H 2 O
[0028] In the above step (11), firstly, the solid phase grinding shearing technique (S 3 M) Solid leather waste (LSM) is prepared into LSW fibers (referred to as LFs) by 15 to 20 grinding cycles at a speed of 50 to 80 rpm; then the LSW fibers are screened to obtain LSW powder; the obtained LSW powder is vacuum dried (drying temperature is 90 to 120°C, drying time is 12 to 18 hours), mixed with dopamine in an alkaline buffer solution for reaction, and then washed and dried to obtain modified leather waste powder. The mass ratio of unmodified LSW powder to dopamine is 19 to 21:1. The alkaline buffer is one of Tris buffer or phosphate buffer; the pH value of the buffer is 8 to 9. The above mixing and stirring reaction time is 8 to 10 hours. The above drying conditions are: vacuum drying at 40 to 80°C for 12 to 18 hours.
[0029] In the above step (12), the concentration of the silver nitrate solution is 110-130 g / L. The concentration of the ammonia water is 25%-28%. When the ammonia water is dripped into the silver nitrate solution, the color of the silver nitrate solution changes from transparent to dark brown; when a black precipitate gradually appears, continue to add ammonia water to make the solution transparent again.
[0030] In the above step (13), the mass ratio of glucose, tetrahydrate, potassium sodium tartrate and polyethylene glycol is 10:0.25:0.01; 10-30 mL of anhydrous ethanol is contained in every 100 mL of solution B. The concentration of glucose is 190-210 g / L; the concentration of tetrahydrate and potassium sodium tartrate is 2.75-5.25 g / L; and the concentration of polyethylene glycol is 0.19-0.21 g / L.
[0031] In the above step (14), the anions are reduced and deposited on the surface of the modified leather waste powder to form a dense silver layer. The above drying conditions are: vacuum drying at 40-60°C for 5.5-6.5h. The mass ratio of the unmodified leather waste powder, silver nitrate and glucose is 1:2.8-3.2:4.7-5.3.
[0032] In the above step (15), the solution containing the binder is coated on a support plate (e.g., a PTFE plate), and then the prepared Ag / LSW composite film is placed on top of the solution containing the binder and dried to obtain an Ag / LSW base layer. The above drying conditions are: vacuum drying at 30-50°C for 5.5-6.5 hours. The mass concentration of the binder in the solution containing the binder is 9-11%. The thickness of the Ag / LSW base layer obtained in this step is about 1.7-1.9 cm.
[0033] In the above step (2), the VO 2 The mass ratio of VO to phase change energy storage material is 1:1 to 9. 2 and the phase change energy storage material are stirred and mixed uniformly at 100-140°C; in a preferred implementation, the stirring rate is 250-350 rpm and the stirring time is 1-2 hours. 2 / PCM composite materials, VO 2 The VO 2 The problem of inconvenience in processing. The VO obtained in this step 2 The thickness of the / PCM composite material is about 0.19 to 0.21 cm.
[0034] In the above step (3), the purpose is to convert VO 2The ambient temperature in step (31) and step (32) is preferably 60-140°C, and the temperature is maintained for about 30 min-1.5 h. At this temperature, the phase change energy storage material is first absorbed into the Ag / LSW substrate layer; then, the VO obtained in step (2) is added to the substrate layer. 2 The / PCM composite material is coated on the surface of the Ag / LSW substrate layer (the other side of the Ag / LSW substrate layer without a binder), and the VO 2 Fixed on the surface of Ag / LSW substrate.
[0035] Compared with the prior art, the electromagnetic shielding material capable of realizing intelligent temperature control and the preparation method thereof provided by the present invention have the following beneficial effects:
[0036] 1) The electromagnetic shielding material provided by the present invention is composed of Ag / LSW substrate and VO 2 / PCM layer composite, with Ag / LSW substrate as the base, VO 2 As a switch; realize the first temperature warning of the material in the electromagnetic wave scene, and then through VO 2 Turn on autonomous temperature control to achieve intelligent temperature control;
[0037] 2) The electromagnetic shielding material provided by the present invention has a dense silver layer, thus having good shielding performance against electromagnetic waves;
[0038] 3) The Ag / LSW substrate provided by the present invention can also load phase change energy storage materials, which can store and release energy in the form of latent heat, so that the composite material has excellent temperature control effect;
[0039] 4) The present invention first converts VO 2 With phase change energy storage materials, VO is fixed by phase change energy storage materials 2 , which makes it easier to 2 processing. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 VO prepared in Example 3 of the present invention 2 XRD spectra before and after paraffin addition;
[0041] Figure 2 The XRD spectra of the Ag / LSW substrate layer prepared in Example 3 of the present invention before and after being doped with paraffin wax;
[0042] Figure 3 This is a SEM image of the Ag / LSW substrate layer prepared in Example 3 of the present invention;
[0043] Figure 4VO prepared in Example 3 of the present invention 2 SEM images of / WAX composites;
[0044] Figure 5 This is a comparison chart of the electromagnetic shielding performance of the BCE aerogels prepared in Examples 1, 2, 3, and 4 of the present invention;
[0045] Figure 6 is the phase change enthalpy of the BCE aerogel prepared in Example 3 of the present invention;
[0046] Figure 7 Thermal imaging of the BCE aerogel prepared in Example 3;
[0047] Figure 8 The DSC spectra of the BCE aerogel prepared in Example 3 of the present invention before and after 120 cycles. DETAILED DESCRIPTION
[0048] The following will clearly and completely describe the technical solutions of various embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0049] The materials used in the following examples are as follows:
[0050] Solid leather waste (LSW) from sheepskin was provided by Xuzhou Xingning Leather Co., Ltd. (Jiangsu, China) using a commercial chrome tanning process.
[0051] Polyvinyl alcohol PVA1799 (average degree of polymerization: 1799±50) was purchased from Chengdu Kelong Chemical Co., Ltd.
[0052] Silver nitrate, dopamine hydrochloride, Tris buffer, hydrochloric acid, anhydrous ethanol, potassium sodium tartrate tetrahydrate (C 4 H 4 O 6 KNa·4H 2 O), ammonia (NH 3 ·H2O) and glucose (C 6 H 12 O 6 ·H 2 (0, 98%) was purchased from Chengdu Jinshan Chemical Reagent Co., Ltd. All reagents were used as received without further purification.
[0053] Vanadium(IV) oxide (VO 2 ) was purchased from Wuhan Lullaby Pharmaceutical Chemical Co., Ltd.
[0054] High-efficiency paraffin wax (WAX) was purchased from Shanghai Huayong Paraffin Co., Ltd.
[0055] Unless otherwise specified, the solvents in the solutions described in the following examples are all deionized water.
[0056] Example 1
[0057] The electromagnetic shielding material provided in this embodiment has the following preparation steps:
[0058] (1) Preparation of Ag / LSW substrate layer, including the following steps:
[0059] (11) Using a solid phase mechanochemical reactor, 2 g of LSW was debonded into LSW fibers at a speed of 50 rpm after 15 grinding cycles. The LSW powder was then sieved using a sifter (100 mesh). The obtained LSW powder was vacuum dried at 105 °C for 12 h.
[0060] 0.1212 g of Tris was dissolved in deionized water at room temperature, and the pH was adjusted to about 8.5. Then 0.1 g of dopamine hydrochloride and 2 g of LSW powder were added thereto. The volume was fixed with a 100 mL volumetric flask and magnetically stirred for 8 h to form a polydopamine layer (PDA) on the surface of the LSW powder. The powder was then washed with deionized water and vacuum dried at 40 °C for 12 h to obtain PDA-modified LSW powder.
[0061] (12) Add ammonia water (concentration of 25-28%) to a silver nitrate solution (containing 6 g of silver nitrate) until the solution becomes transparent (place a piece of white paper under the container for observation), and then continue to add deionized water to make up the volume to obtain 50 mL of solution A. The concentration of silver nitrate is 120 g / L.
[0062] (13) A mixture containing 10 g of glucose, 0.25 g of tetrahydrate and potassium sodium tartrate (C 4 H 4 O 6 KNa·4H 2 O), 0.01g polyethylene glycol 1000 and 10mL anhydrous ethanol were mixed with deionized water to make the volume 50mL, and then mixed evenly to obtain 50mL solution B; the concentration of glucose was 200g / L, the concentration of tetrahydrate and potassium sodium tartrate was 5g / L, and the concentration of polyethylene glycol 1000 was 0.2g / L.
[0063] (14) The modified LSW powder obtained in step (11) was mixed with 50 mL of solution A and 50 mL of solution B, magnetically stirred for 0.5 h, then soaked and allowed to stand for 6 h, and the resulting powder was washed with deionized water and vacuum dried at 40 °C for 6 h to obtain an Ag / LSW composite material.
[0064] (15) The Ag / LSW composite material obtained in step (14) was uniformly dispersed in 100 mL of deionized water, and the resulting dispersion was vacuum filtered to obtain an Ag / LSW composite membrane; about 4 mL of PVA solution (PVA concentration was 10 wt%) was coated on a PTFE plate, and then the prepared Ag / LSW composite membrane was placed on top of the PVA solution, and vacuum dried at 40°C for 6 h to obtain an Ag / LSW base layer with a thickness of 1.8 cm.
[0065] (2) Paraffin was placed on top of the Ag / LSW substrate in an oven at 80°C and heated for about 1 h until the paraffin was absorbed into the Ag / LSW substrate. The paraffin accounted for 26% of the total mass of the Ag / LSW substrate and paraffin. 2 , so it is recorded as BCJ fabric-0.
[0066] Example 2
[0067] The electromagnetic shielding material provided in this embodiment has the following preparation steps:
[0068] (1) Preparation of Ag / LSW substrate layer, including the following steps:
[0069] (11) Using a solid phase mechanochemical reactor, 2 g of LSW was debonded into LSW fibers at a speed of 50 rpm after 15 grinding cycles. The LSW powder was then sieved using a sifter (100 mesh). The obtained LSW powder was vacuum dried at 105 °C for 12 h.
[0070] 0.1212 g of Tris was dissolved in deionized water at room temperature, and the pH was adjusted to about 8.5. Then 0.1 g of dopamine hydrochloride and 2 g of LSW powder were added thereto. The volume was fixed with a 100 mL volumetric flask and magnetically stirred for 8 h to form a polydopamine layer (PDA) on the surface of the LSW powder. The powder was then washed with deionized water and vacuum dried at 40 °C for 12 h to obtain PDA-modified LSW powder.
[0071] (12) Add ammonia water (concentration of 25-28%) to a silver nitrate solution (containing 6 g of silver nitrate) until the solution becomes transparent (place a piece of white paper under the container for observation), and then continue to add deionized water to make up the volume to obtain 50 mL of solution A. The concentration of silver nitrate is 120 g / L.
[0072] (13) A mixture containing 10 g of glucose, 0.25 g of tetrahydrate and potassium sodium tartrate (C 4 H 4 O 6 KNa·4H 2O), 0.01g polyethylene glycol 1000 and 10mL anhydrous ethanol were mixed with deionized water to make the volume 50mL, and then mixed evenly to obtain 50mL solution B; the concentration of glucose was 200g / L, the concentration of tetrahydrate and potassium sodium tartrate was 5g / L, and the concentration of polyethylene glycol 1000 was 0.2g / L.
[0073] (14) The modified LSW powder obtained in step (11) was mixed with 50 mL of solution A and 50 mL of solution B, magnetically stirred for 1 h, and then soaked and allowed to stand for 8 h. The resulting powder was then washed with deionized water and vacuum dried at 40 °C for 6 h to obtain an Ag / LSW composite material.
[0074] (15) The Ag / LSW composite material obtained in step (14) was uniformly dispersed in 100 mL of deionized water, and the resulting dispersion was vacuum filtered to obtain an Ag / LSW composite membrane; about 4 mL of PVA solution (PVA concentration was 10 wt%) was coated on a PTFE plate, and then the prepared Ag / LSW composite membrane was placed on top of the PVA solution, and vacuum dried at 40°C for 6 h to obtain an Ag / LSW base layer with a thickness of 1.8 cm.
[0075] (2) VO 2 Preparation of WAX composite materials
[0076] VO 2 and paraffin wax in a mass ratio of 1:9 were placed in a beaker and mechanically stirred at 250 rpm in an oil bath at 120 °C for 1 h to obtain VO 2 / WAX composite material.
[0077] (3) Ag / LSW substrate and VO 2 The method of preparing electromagnetic shielding materials by composite of WAX composite material includes the following steps:
[0078] (31) Paraffin wax was placed on top of the Ag / LSW substrate in an oven at 80 °C and heated for approximately 1 h until the paraffin wax was absorbed into the Ag / LSW substrate and the paraffin wax accounted for 26% of the total mass of the Ag / LSW substrate and paraffin wax.
[0079] (32) The hot VO mixed in step (2) 2 The / WAX composite material was directly coated on the upper surface of the Ag / LSW substrate layer (thickness of 0.2 cm), then placed in an oven at 80°C and heated for about 1 h, and then cooled at room temperature to obtain an electromagnetic shielding material, which was recorded as BCJ fabric-10.
[0080] Example 3
[0081] The electromagnetic shielding material provided in this embodiment has the following preparation steps:
[0082] (1) Preparation of Ag / LSW substrate layer, including the following steps:
[0083] (11) Using a solid phase mechanochemical reactor, 2 g of LSW was finally debonded into LSW fibers at a speed of 50 rpm after 15 grinding cycles. The fibers were then sieved using a sifter (100 mesh) to obtain LSW powder. The obtained LSW powder was vacuum dried at 105 °C for 12 h.
[0084] 0.1212 g of Tris was dissolved in deionized water at room temperature, and the pH was adjusted to about 8.5. Then 0.1 g of dopamine hydrochloride and 2 g of LSW powder were added thereto. The volume was fixed with a 100 mL volumetric flask and magnetically stirred for 8 h to form a polydopamine layer (PDA) on the surface of the LSW powder. The powder was then washed with deionized water and vacuum dried at 40 °C for 12 h to obtain PDA-modified LSW powder.
[0085] (12) Add ammonia water (concentration of 25-28%) dropwise into 150 mL of silver nitrate solution (containing 6 g of silver nitrate) until the solution becomes transparent (place a piece of white paper under the container for observation), and then continue to add deionized water to make up the volume to obtain 50 mL of solution A with a silver nitrate concentration of 120 g / L.
[0086] (13) A mixture containing 10 g of glucose, 0.25 g of tetrahydrate and potassium sodium tartrate (C 4 H 4 O 6 KNa·4H 2 O), 0.01g polyethylene glycol 1000 and 10mL anhydrous ethanol were mixed with deionized water to make the volume 50mL, and then mixed evenly to obtain 50mL solution B; the concentration of glucose was 200g / L, the concentration of tetrahydrate and potassium sodium tartrate was 5g / L, and the concentration of polyethylene glycol 1000 was 0.2g / L.
[0087] (14) The modified LSW powder obtained in step (11) was mixed with 50 mL of solution A and 50 mL of solution B, magnetically stirred for 0.5 h, then soaked and allowed to stand for 6 h, and the resulting powder was washed with deionized water and vacuum dried at 40 °C for 6 h to obtain an Ag / LSW composite material.
[0088] (15) The Ag / LSW composite material obtained in step (14) was uniformly dispersed in 100 mL of deionized water, and the obtained dispersion was vacuum filtered to obtain an Ag / LSW composite membrane; about 4 mL of PVA solution (PVA concentration was 10 wt%) was coated on a PTFE plate, and then the prepared Ag / LSW composite membrane was placed on the top of the PVA solution, and vacuum dried at 40°C for 6 h to obtain an Ag / LSW base layer with a thickness of 1.8 cm.
[0089] (2) VO2 Preparation of WAX composite materials
[0090] VO 2 and paraffin wax in a mass ratio of 1:3 were placed in a beaker and mechanically stirred at 350 rpm in an oil bath at 120 °C for 2 h to obtain VO 2 / WAX composite material.
[0091] (3) Ag / LSW substrate and VO 2 The method of preparing electromagnetic shielding materials by composite of WAX composite material includes the following steps:
[0092] (31) Paraffin wax was placed on top of the Ag / LSW substrate in an oven at 80 °C and heated for approximately 1 h until the paraffin wax was absorbed into the Ag / LSW substrate and the paraffin wax accounted for 26% of the total mass of the Ag / LSW substrate and paraffin wax.
[0093] (32) The hot VO mixed in step (2) 2 The / WAX composite material was directly coated on the upper surface of the Ag / LSW substrate layer (thickness of 0.2 cm), then placed in an oven at 80°C and heated for about 1 h, and then cooled at room temperature to obtain an electromagnetic shielding material, which was recorded as BCJ fabric-25.
[0094] Example 4
[0095] The electromagnetic shielding material provided in this embodiment has the following preparation steps:
[0096] (1) Preparation of Ag / LSW substrate layer, including the following steps:
[0097] (11) Using a solid phase mechanochemical reactor, 2 g of LSW was finally debonded into LSW fibers at a speed of 50 rpm after 15 grinding cycles. The fibers were then sieved using a sifter (100 mesh) to obtain LSW powder. The obtained LSW powder was vacuum dried at 105 °C for 12 h.
[0098] 0.1212 g of Tris was dissolved in deionized water at room temperature, and the pH was adjusted to about 8.5. Then 0.1 g of dopamine hydrochloride and 2 g of LSW powder were added thereto. The volume was fixed with a 100 mL volumetric flask and magnetically stirred for 8 h to form a polydopamine layer (PDA) on the surface of the LSW powder. The powder was then washed with deionized water and vacuum dried at 40 °C for 12 h to obtain PDA-modified LSW powder.
[0099] (12) Add ammonia water (concentration of 25-28%) to a silver nitrate solution (containing 6 g of silver nitrate) until the solution becomes transparent (place a piece of white paper under the container for observation), and then continue to add deionized water to make up the volume to obtain 50 mL of solution A. The concentration of silver nitrate is 120 g / L.
[0100] (13) A mixture containing 10 g of glucose, 0.25 g of tetrahydrate and potassium sodium tartrate (C 4 H 4 O 6 KNa·4H 2 O), 0.01g polyethylene glycol 1000 and 10mL anhydrous ethanol were mixed with deionized water to make the volume 50mL, and then mixed evenly to obtain 50mL solution B; the concentration of glucose was 200g / L, the concentration of tetrahydrate and potassium sodium tartrate was 5g / L, and the concentration of polyethylene glycol 1000 was 0.2g / L.
[0101] (14) The modified LSW powder obtained in step (11) was mixed with 50 mL of solution A and 50 mL of solution B, magnetically stirred for 0.5 h, then soaked and allowed to stand for 6 h, and the resulting powder was washed with deionized water and vacuum dried at 40 °C for 6 h to obtain an Ag / LSW composite material.
[0102] (15) The Ag / LSW composite material obtained in step (14) was uniformly dispersed in 100 mL of deionized water, and the obtained dispersion was vacuum filtered to obtain an Ag / LSW composite membrane; about 4 mL of PVA solution (PVA concentration was 10 wt%) was coated on a PTFE plate, and then the prepared Ag / LSW composite membrane was placed on the top of the PVA solution, and vacuum dried at 40°C for 6 h to obtain an Ag / LSW base layer with a thickness of 1.8 cm.
[0103] (2) VO 2 Preparation of WAX composite materials
[0104] VO 2 and paraffin wax in a mass ratio of 1:1 were placed in a beaker and mechanically stirred at 300 rpm in an oil bath at 120 °C for 1 h to obtain VO 2 / WAX composite material.
[0105] (3) Ag / LSW substrate and VO 2 The method of preparing electromagnetic shielding materials by composite of WAX composite material includes the following steps:
[0106] (31) Paraffin wax was placed on top of the Ag / LSW substrate in an oven at 80 °C and heated for approximately 1 h until the paraffin wax was absorbed into the Ag / LSW substrate and the paraffin wax accounted for 26% of the total mass of the Ag / LSW substrate and paraffin wax.
[0107] (32) The hot VO mixed in step (2) 2The / WAX composite material was directly coated on the upper surface of the Ag / LSW substrate layer (thickness of 0.2 cm), then placed in an oven at 80°C and heated for about 1 h, and then cooled at room temperature to obtain an electromagnetic shielding material, which was recorded as BCJ fabric-50.
[0108] Example 5
[0109] The electromagnetic shielding material provided in this embodiment has the following preparation steps:
[0110] (1) Preparation of Ag / LSW substrate layer, including the following steps:
[0111] (11) Using a solid phase mechanochemical reactor, 2 g of LSW was finally debonded into LSW fibers at a speed of 50 rpm after 15 grinding cycles. The fibers were then sieved using a sifter (100 mesh) to obtain LSW powder. The obtained LSW powder was vacuum dried at 105 °C for 12 h.
[0112] 0.1212 g of Tris was dissolved in deionized water at room temperature and the pH was adjusted to about 8.5. Then 0.1 g of dopamine hydrochloride and 2 g of LSW powder were added thereto. The volume was fixed with a 100 mL volumetric flask and magnetically stirred for 8 h to form a polydopamine layer (PDA) on the surface of the LSW powder. The powder was then washed with deionized water and vacuum dried at 80 °C for 12 h to obtain PDA-modified LSW powder.
[0113] (12) Add ammonia water (concentration of 25-28%) dropwise into a silver nitrate solution (containing 5.6 g of silver nitrate) until the solution becomes transparent (place a piece of white paper under the container for observation). Then continue to add deionized water to make up the volume to obtain 50 mL of solution A. The concentration of silver nitrate is 112 g / L.
[0114] (13) A mixture containing 10 g of glucose, 0.25 g of tetrahydrate and potassium sodium tartrate (C 4 H 4 O 6 KNa·4H 2 O), 0.01g polyethylene glycol 1000 and 5mL anhydrous ethanol were added with deionized water to make the volume to 50mL, and then mixed evenly to obtain 50mL solution B; the concentration of glucose was 200g / L, the concentration of tetrahydrate and potassium sodium tartrate was 5g / L, and the concentration of polyethylene glycol 1000 was 0.2g / L.
[0115] (14) The modified LSW powder obtained in step (11) was mixed with 50 mL of solution A and 50 mL of solution B, magnetically stirred for 0.5 h, then soaked and allowed to stand for 8 h, and the resulting powder was washed with deionized water and vacuum dried at 60 °C for 5.5 h to obtain an Ag / LSW composite material.
[0116] (15) The Ag / LSW composite material obtained in step (14) was uniformly dispersed in 100 mL of deionized water, and the obtained dispersion was vacuum filtered to obtain an Ag / LSW composite membrane; about 4 mL of PVP solution (PVP concentration was 10 wt%) was coated on a PTFE plate, and then the prepared Ag / LSW composite membrane was placed on top of the PVP solution, and vacuum dried at 50°C for 6 h to obtain an Ag / LSW base layer with a thickness of 1.8 cm.
[0117] (2) VO 2 Preparation of WAX composite materials
[0118] VO 2 and paraffin wax in a mass ratio of 1:9 were placed in a beaker and mechanically stirred at 300 rpm in an oil bath at 100 °C for 2 h to obtain VO 2 / WAX composite material.
[0119] (3) Ag / LSW substrate and VO 2 The method of preparing electromagnetic shielding materials by composite of WAX composite material includes the following steps:
[0120] (31) Paraffin wax was placed on top of the Ag / LSW substrate in an oven at 60 °C and heated for approximately 1.5 h until the paraffin wax was absorbed into the Ag / LSW substrate and accounted for 20% of the total mass of the Ag / LSW substrate and paraffin wax.
[0121] (32) The hot VO mixed in step (2) 2 The / WAX composite material is directly coated on the upper surface of the Ag / LSW substrate layer (thickness is 0.2 cm), and then placed in an oven at 60°C, heated for about 1.5 hours, and then cooled at room temperature to obtain an electromagnetic shielding material.
[0122] Example 6
[0123] The electromagnetic shielding material provided in this embodiment has the following preparation steps:
[0124] (1) Preparation of Ag / LSW substrate layer, including the following steps:
[0125] (11) Using a solid phase mechanochemical reactor, 2 g of LSW was finally debonded into LSW fibers at a speed of 50 rpm after 15 grinding cycles. The fibers were then sieved using a sifter (100 mesh) to obtain LSW powder. The obtained LSW powder was vacuum dried at 105 °C for 12 h.
[0126] 0.1212 g of Tris was dissolved in deionized water at room temperature and the pH was adjusted to about 8.5. Then 0.1 g of dopamine hydrochloride and 2 g of LSW powder were added thereto. The volume was fixed with a 100 mL volumetric flask and magnetically stirred for 8 h to form a polydopamine layer (PDA) on the surface of the LSW powder. The powder was then washed with deionized water and vacuum dried at 60 °C for 18 h to obtain PDA-modified LSW powder.
[0127] (12) Add ammonia water (concentration of 25-28%) dropwise into a silver nitrate solution (containing 6.4 g of silver nitrate) until the solution becomes transparent (place a piece of white paper under the container for observation). Then continue to add deionized water to make up the volume to obtain 50 mL of solution A. The concentration of silver nitrate is 128 g / L.
[0128] (13) A mixture containing 10 g of glucose, 0.25 g of tetrahydrate and potassium sodium tartrate (C 4 H 4 O 6 KNa·4H 2 O), 0.01g polyethylene glycol 1000 and 15mL anhydrous ethanol were added with deionized water to make up to 50mL, and then mixed evenly to obtain 50mL solution B; the concentration of glucose was 200g / L, the concentration of tetrahydrate and potassium sodium tartrate was 5g / L, and the concentration of polyethylene glycol 1000 was 0.2g / L.
[0129] (14) The modified LSW powder obtained in step (11) was mixed with 50 mL of solution A and 50 mL of solution B, magnetically stirred for 0.5 h, then soaked and allowed to stand for 8 h, and the resulting powder was washed with deionized water and vacuum dried at 40 °C for 6.5 h to obtain an Ag / LSW composite material.
[0130] (15) The Ag / LSW composite material obtained in step (14) was uniformly dispersed in 100 mL of deionized water, and the obtained dispersion was vacuum filtered to obtain an Ag / LSW composite membrane; about 4 mL of PAA solution (PAA concentration was 10 wt%) was coated on a PTFE plate, and then the prepared Ag / LSW composite membrane was placed on the top of the PAA solution, and vacuum dried at 50°C for 6 h to obtain an Ag / LSW base layer with a thickness of 1.8 cm.
[0131] (2) VO 2 Preparation of WAX composite materials
[0132] VO 2 and paraffin wax in a mass ratio of 1:1 were placed in a beaker and mechanically stirred at 300 rpm in an oil bath at 140 °C for 1 h to obtain VO 2 / WAX composite material.
[0133] (3) Ag / LSW substrate and VO2 The method of preparing electromagnetic shielding materials by composite of WAX composite material includes the following steps:
[0134] (31) Paraffin wax was placed on top of the Ag / LSW substrate in an oven at 140 °C and heated for approximately 30 min until the paraffin wax was absorbed into the Ag / LSW substrate and accounted for 23% of the total mass of the Ag / LSW substrate and paraffin wax.
[0135] (32) The hot VO mixed in step (2) 2 The / WAX composite material is directly coated on the upper surface of the Ag / LSW substrate layer (thickness is 0.2 cm), and then placed in an oven at 140° C., heated for about 30 minutes, and then cooled at room temperature to obtain an electromagnetic shielding material.
[0136] The structure and performance of the electromagnetic shielding materials prepared in some of the above embodiments are characterized.
[0137] (I) Structural characterization
[0138] About VO 2 And the VO prepared in Example 3 2 / WAX composite material was subjected to XRD test, and the test results are as follows Figure 1 As shown. Figure 1 It can be seen that the target product VO 2 / WAX composite material was successfully prepared. 2 / WAX composite material was subjected to SEM test, and the results are as follows Figure 4 As shown, from Figure 4 It can be seen that VO 2 It compounds well with paraffin wax (WAX) and is easy to process.
[0139] The Ag / LSW substrate prepared in Example 3 was subjected to XRD test before and after paraffin absorption. The test results are shown in FIG. Figure 2 As shown. Figure 2 It can be seen that paraffin is successfully loaded in the Ag / LSW substrate layer, which can provide phase change energy storage function and realize intelligent temperature control.
[0140] The Ag / LSW substrate prepared in Example 3 was tested by SEM. The results are as follows: Figure 3 As shown, from Figure 3 It can be seen that there is a dense silver layer wrapped on the surface of LSW fiber in the Ag / LSW substrate. Since silver can provide electromagnetic shielding performance, the substrate has good electromagnetic shielding properties.
[0141] (II) Electromagnetic shielding performance
[0142] The electromagnetic shielding performance of the electromagnetic shielding materials prepared in Examples 1, 2, 3, and 4 was characterized and compared. The results are as follows: Figure 5 shown.
[0143] As can be seen from the figure, when VO is not set 2 / WAX layer, the electromagnetic shielding effect is general; when setting VO 2 / WAX layer, the electromagnetic shielding performance is significantly improved.
[0144] (III) Thermal performance
[0145] The electromagnetic shielding material BCJ fabric-25 prepared in Example 3 was subjected to phase change enthalpy, thermal imaging and DSC cycle tests. The results are as follows: Figure 6 , Figure 7 , Figure 8 shown.
[0146] From the phase change enthalpy test, it can be seen that BCJ aerogel has high melting enthalpy and high crystallization enthalpy, which gives it excellent thermal management capabilities.
[0147] In the thermal imaging experiment, the BCJ aerogel was irradiated with an infrared lamp to simulate the actual application scenario. By comparing high-power and low-power irradiation, the BCJ aerogel showed different response speeds, and rapid heating was observed under high-power irradiation. At the same time, the phase change platform that appeared during the heating and cooling of the BCJ aerogel was consistent with the results of the differential scanning calorimeter (DSC) test.
[0148] Excellent durability is a necessary condition to ensure that BCJ aerogel has a long service life, which is also very important for evaluating the applicability of the material. The durability of BCJ aerogel was evaluated by cyclic DSC experiments. Figure 8 The DSC curve after 120 cycles almost coincides with the original curve, indicating that the BCE aerogel has excellent thermal reliability.
[0149] Those skilled in the art will appreciate that the embodiments herein are intended to help readers understand the principles of the present invention, and should be understood that the protection scope of the present invention is not limited to such specific statements and embodiments. Those skilled in the art can make various other specific variations and combinations that do not deviate from the essence of the present invention based on the technical revelations disclosed by the present invention, and these variations and combinations are still within the protection scope of the present invention.
Claims
1. An electromagnetic shielding material capable of realizing intelligent temperature control, characterized in that: The invention comprises an Ag / LSW substrate layer, a phase change energy storage material absorbed into the Ag / LSW substrate layer and VO2 adsorbed on the surface of the Ag / LSW substrate layer; the Ag / LSW substrate layer is obtained by compounding Ag and leather waste via a binder.
2. The electromagnetic shielding material capable of realizing intelligent temperature control according to claim 1, characterized in that: The Ag / LSW substrate layer presents a three-dimensional porous structure.
3. The electromagnetic shielding material capable of realizing intelligent temperature control according to claim 1, characterized in that: In the Ag / LSW base layer, the mass ratio of Ag to unmodified leather waste LSW is 1.8-2.0:
1.
4. The electromagnetic shielding material capable of realizing intelligent temperature control according to any one of claims 1 to 3, characterized in that: The leather waste is leather waste powder modified by polydopamine.
5. The electromagnetic shielding material capable of realizing intelligent temperature control according to claim 4, characterized in that: The dopamine can be replaced by vitamin C or catechol; the leather waste can be replaced by cellulose, palm leather, and Lino leather; the binder used to bond Ag and leather waste is one of polyvinyl alcohol, polyvinyl pyrrolidone, carboxymethyl cellulose, and polyacrylic acid; the phase change energy storage material is paraffin, coconut oil, or dodecanol.
6. The electromagnetic shielding material capable of realizing intelligent temperature control according to claim 4, characterized in that: The phase-change energy storage material absorbed in the Ag / LSW substrate layer accounts for at least 20% of the total mass of the Ag / LSW substrate layer and the absorbed phase-change energy storage material.
7. The method for preparing an electromagnetic shielding material capable of realizing intelligent temperature control according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Preparation of Ag / LSW substrate layer, including the following steps: (11) preparing leather waste powder and modifying it by polydopamine to obtain modified leather waste powder; (12) preparing solution A: under stirring, adding aqueous ammonia to the silver nitrate solution until the solution becomes transparent to obtain solution A; (13) preparing solution B: mixing glucose, tetrahydrate, potassium sodium tartrate, polyethylene glycol and anhydrous ethanol in water to obtain solution B; (14) mixing the modified leather waste powder with solution A and solution B, stirring and mixing evenly, and then standing for 6 to 8 hours, and then washing and drying to obtain an Ag / LSW composite material; (15) uniformly dispersing the Ag / LSW composite material in water, and then vacuum filtering the obtained dispersion to obtain an Ag / LSW composite film; the Ag / LSW composite film is fixed by a binder to obtain an Ag / LSW substrate layer; (2) Preparation of VO2 / PCM composite materials The VO2 and the phase change energy storage material are stirred and mixed at a temperature higher than the melting point of the phase change energy storage material to obtain a VO2 / PCM composite material; (3) Ag / LSW substrate layer and VO2 / PCM composite material are composited to prepare electromagnetic shielding material, including the following steps: (31) At an ambient temperature higher than the melting point of the phase change energy storage material, the phase change energy storage material is absorbed into the Ag / LSW substrate layer; (32) At an ambient temperature higher than the melting point of the phase change energy storage material, the VO2 / PCM composite material obtained in step (2) is compounded onto the surface of the Ag / LSW substrate layer, and then cooled at room temperature to obtain an electromagnetic shielding material.
8. The method for preparing an electromagnetic shielding material capable of realizing intelligent temperature control according to claim 7, characterized in that: In step (11), solid leather waste is first prepared into LSW fibers by solid phase grinding and shearing technology through 15 to 20 grinding cycles at a speed of 50 to 80 rpm; then the LSW fibers are sieved to obtain LSW powder; the obtained LSW powder is vacuum dried, mixed and stirred with dopamine in an alkaline buffer solution, and then washed and dried to obtain modified leather waste powder; the mass ratio of the LSW powder to dopamine is 19 to 21:
1.
9. The method for preparing an electromagnetic shielding material capable of realizing intelligent temperature control according to claim 7, characterized in that: In step (13), the mass ratio of glucose, tetrahydrate, sodium potassium tartrate and polyethylene glycol is 10:0.25:0.
01.
10. The method for preparing an electromagnetic shielding material capable of realizing intelligent temperature control according to claim 7, characterized in that: In step (2), the mass ratio of VO2 to phase change energy storage material is 1:1 to 9.
11. The method for preparing an electromagnetic shielding material capable of realizing intelligent temperature control according to claim 7, characterized in that: In step (2), VO2 and the phase change energy storage material are stirred and mixed uniformly at 100-140°C; the ambient temperature in steps (31) and (32) is 60-140°C.
Citation Information
Patent Citations
Low-reflection and high-absorption electromagnetic shielding material and preparation method thereof
CN109022638A
Discarded leather superfine fiber, high electromagnetic shielding material combined with discarded leather superfine fiber and polyvinyl alcohol and preparation methods of discarded leather superfine fiber and high electromagnetic shielding material
CN111424341A
Electromagnetic shielding composite material with temperature response characteristic and preparation method and application thereof
CN115322442A
Methods and compositions for metal nanoparticle treated surfaces
EP1991365A2
Light-emitting element, light-emitting device, lighting device, and electronic appliance
TW201545390A